Flavonoid Constituents of Cakile maritima (Scope) Growing in Egypt and Their Biological Activity - A. Shams, Khaled; M. Radwan, Hany; A. Tawfik, Wafaa; A. Habib, Amira; M. Soliman, Abdel-Mohsen (Asian Journal of Chemistry, 2010)
The study of the flavonoidal constituents isolated from the chloroform, ethyl acetate and butanol fractions of aqueous alcoholic extract of Cakile maritima (family Crucifereae) revealed the isolation and identification of quercetin, quercetin-3-O-rhamnoside, kaempferol-7-O-glucoside, luteolin, luteolin-7-O-glucoside and caffeic acid. Identification of the isolated compounds was carried out by spectroscopic analysis viz UV, MS, NMR, TLC, PC and acid hydrolysis of the glycoside compounds. The radical scavenging effects of the tested extracts and isolated compounds on DPPH free radical were observed, in which the flavonoidal compounds showed a strong antioxidant activity. Molluscidal activity of different fractions and isolated compounds of Cakile maritime was carried out against Biomphalaria alexandrina snails, in which luteolin- 7-O-glucoside, kaempferol-7-O-glucoside and quercetin-3-O-rhamnoside showed significant molluscicidal activity (LC50 24, 37 and 40, respectively). It was also found that the quercetin, luteolin and caffeic acid had showed moderate activity.